دور مجلس الإدارة في مراقبة تطبيق حوكمة الشركات في المؤسسة الجزائرية للأقمشة الصناعية والتقنيةeatit - غلاب, فاتح (جامعة الوادي University of Eloued, 2019)
The importance of social responsibility has become significant now a day. In fact, the major institutions are seeking to improve the level of their business as well as the well-being of society by paying attention to social responsibility. Therefore, it has been given a special accountability called “accountability for social responsibility”, which has specific hypotheses and principles. Also, it has several records about the social status of the employees in the institution. Moreover, the institutions have assumed responsibility in compensating for the damage caused by theiractivities and the resulting pollution. It bears the responsibility of spreading a culture of social responsibility and commitment to moral and social standards. The objective of this studyis to identify the most important areas of accountability for social responsibility and its objectives, as well as to address the problemsfaced by this process, on the one hand, and to focus on the concept of social auditing, whichworks to highlight the reality of the adoption of social responsibility by business organizations, on the other hand.
Accounting for social responsibility and social auditing
مقال
Keywords: حوكمة الشركات، مجلس الإدارة، المساهمين وحقوق المساهمين، إدارة الشركة، الإفصاح والشفافية.; Key words: corporate governance, board of directors, shareholders and shareholders' equity, company management, disclosure and transparency..